DETERMINAN PERILAKU KONSUMEN SMARTPHONE PADA SISWA SMA NEGERI DI KOTA SALATIGA - Fitriana, Ana; Widodo, Joko; Pujiati, Amin (Journal of Economic Education, 2015)
Siswa SMA memiliki gaya hidup yang cenderung konsumtif dalam penggunaan smartphone. Penelitian ini bertujuan untuk mengetahui pengaruh faktor psikologi, faktor situasional dan faktor sosial terhadap perilaku konsumen smartphone pada siswa SMAN di kota Salatiga. Data dalam penelitian ini menggunakan data primer dengan populasi 2902 siswa dan sampel 97 siswa. Variabel yang digunakan perilaku konsumen sebagai variabel terikat dan faktor psikologi, faktor situasional dan faktor sosial sebagai variabel bebas. Teknik pengumpulan data menggunakan kuesioner dengan alat analisis regresi. Hasil penelitian menunjukkan bahwa faktor psikologi, faktor sosial berpengaruh terhadap perilaku konsumen, sedangkan faktor situasional tidak berpengaruh terhadap perilaku konsumen.Â The Â adolescents, especially high school students have a lifestyle that tends to behave consumptive and consumption activities that are not rational. Mostly they do not only owning one just smartphone but most themses have more than one smartphone. It is of course this matter of this matter will become interesting study to be checked furthermore. This research aims to determine the influence of psychological factors, situational factors and social factors to the smartphone consumer behavior in high school students of Salatiga. The population in this study were 2902 students with a sample of 97 students. The independent variable in this study consisted of psychological factors, situational factors and social factors and the dependent variable in the form of consumer behavior. Technique data collecting in this research use kuesioner while technique analyse data use quantitative descriptive technique, and technique analyse doubled linear regresi. The results showed that psychological positive and significant effect on consumer behavior. Situasioanal factors had no effect on consumer behavior, it is certainly contrary to the research Ashraf (2014) explains that the situational factors that most influence on consumer behavior. Social factors positive and significant impact on consumer behavior